Clinical manifestation and diagnostic challenges of SAPHO Syndrome: a case report - Busanello Spanevello, Thami Ellen; Rodrigues, Lucas Teodoro; Rosa Scalcon, Márcia Regina (Brazilian Journal of Case Reports, 2024)
The SAPHO syndrome, characterized by synovitis, acne, pustulosis, hyperostosis, and osteitis, is a rare disease of unknown prevalence and probably underdiagnosed. Its diagnosis can be confirmed by correlating the clinical symptoms with the radiological findings. However, it is challenging to do so since the clinical manifestations of this disease are diverse, with no confirmatory serological marker, and the radiological alterations can be nonspecific. This study is aimed to report the case of a patient with SAPHO syndrome, with an unusual clinical presentation, and the challenges faced to establish the diagnosis.